TELEOLOGY IN ARISTOTLE'S PRACTICAL PHILOSOPHY - Knoll, Manuel (2022)
This article contributes to the debate on the relation of Aristotle’s practical and theoretical philosophy. It argues that his practical philosophy depends to a considerable extent on his teleological conception of nature. This thesis is primarily directed against scholars who maintain that Aristotle does not derive political and human relations from natural or cosmic conditions. The paper defends David Sedley’s anthropocentric interpretation of Aristotle’s natural teleology and shows how Aristotle applies teleological explanations to power relations among human beings – among men and women and among freemen and natural slaves – and their purposes and goals. The article focuses on Aristotle’s human ‘function’ (ergon) argument, which is a teleological argument at the center of his practical philosophy. It argues that this argument, which Aristotle presents to define ‘human flourishing’ or ‘happiness’ (eudaimonia), depends on his definition of man as the only ‘living being that has language and reason’ (zôon logon echon). It further claims that the dispute about whether Aristotle identifies eudaimonia only with a life of contemplation or whether eudaimonia includes a political life can be clarified by referring to the natural purpose of logos.